2007
DOI: 10.1128/jcm.00913-07
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Six Antimicrobial Susceptibility Methods for Testing Linezolid against Staphylococci and Enterococci

Abstract: A challenge panel of enterococci (n ‫؍‬ 50) and staphylococci (n ‫؍‬ 50), including 17 and 15 isolates that were nonsusceptible to linezolid, respectively, were tested with the Clinical and Laboratory Standards Institute broth microdilution and disk diffusion reference methods. In addition, all 100 isolates were tested in parallel by Etest (AB Biodisk, Solna, Sweden), MicroScan WalkAway (Dade, West Sacramento, CA), BD Phoenix (BD Diagnostic Systems, Sparks, MD), VITEK (bioMérieux, Durham, NC), and VITEK 2 (bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 25 publications
5
37
0
Order By: Relevance
“…They compared seven methods, the Vitek, Vitek2, Microscan WalkAway, BD Phoenix (BD Diagnostic Systems, Sparks, MD), Etest, disk diffusion, and broth microdilution (16). As in our study, they found that there was poor categorical agreement between methods.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…They compared seven methods, the Vitek, Vitek2, Microscan WalkAway, BD Phoenix (BD Diagnostic Systems, Sparks, MD), Etest, disk diffusion, and broth microdilution (16). As in our study, they found that there was poor categorical agreement between methods.…”
Section: Discussionmentioning
confidence: 63%
“…Linezolid is a bacteriostatic antibiotic and as such can generate susceptibility patterns that can be challenging to interpret (16,17). Etest, for example, requires that 90% inhibition be considered when determining the MIC, while disk diffusion requires the use of transmitted light.…”
Section: Discussionmentioning
confidence: 99%
“…Although hazy colonies or microcolonies were not observed on MH agar by the agar dilution method, these appeared on BHI agar in some strains. Previous studies have reported the following: (i) an MRSA strain with a cfr mutation with a linezolid MIC of 8 mg l 21 obtained by the agar dilution method showed a faint halo of growth with the Etest method and the MIC was difficult to read (Arias et al, 2008); (ii) the MICs of linezolid by Etest in linezolid-susceptible clinical isolates appeared to be one to two dilution values lower than those obtained by the microdilution method (Tubau et al, 2001); and (iii) the MIC reading by the disc diffusion and Etest methods in staphylococci needs to be improved (Tenover et al, 2007). The results reported in these studies are consistent with the present results, although a solution for these difficulties remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…This was also true for the antibiotics with restricted use due to high cost, such as imipenen (2%) and linezolide (7%) ( Table 2). Tenover et al (2007) comparing the most commonly used susceptibility testing methods challenged with linezolid-non susceptible staphylococci, concluded that generally the problem was much greater in the non-detection of resistance rather than a possible overcalling of resistance. For this study, the criterium adopted to report linezolide resistance followed CLSI standards that consider any discernible growth within the zone of inhibition as indicative of resistance to linezolide.…”
Section: Resultsmentioning
confidence: 99%